2019
DOI: 10.2174/2211352516666181008114542
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Exploitation of Non-Steroidal Anti-inflammatory Drugs as Potential Sources of Novel Antibacterial Agents

Abstract: The ever-increasing threat of bacterial infections and antimicrobial resistance calls for a global effort to deal with this problem. This fast and universal dissemination of antimicrobialresistant bacterial strains resulted in the diminution of therapeutic alternatives for various infectious diseases. Besides, the unaffordability of efficacious antimicrobials coupled with the occurrence of unpleasant adverse effects calls for the exploration of alternative agents with possible antibacterial effect. All these c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…In addition, it has been documented that these non-antibiotic pharmaceuticals can have antimicrobial effects in vivo. NSAIDs have been assessed as potential sources of novel antibacterial agents in vivo [ 80 ]. For example, diclofenac protected mice from virulent Salmonella infection [ 81 ], and ibuprofen demonstrated antimicrobial activity against Candida albicans in mouse kidney models [ 82 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has been documented that these non-antibiotic pharmaceuticals can have antimicrobial effects in vivo. NSAIDs have been assessed as potential sources of novel antibacterial agents in vivo [ 80 ]. For example, diclofenac protected mice from virulent Salmonella infection [ 81 ], and ibuprofen demonstrated antimicrobial activity against Candida albicans in mouse kidney models [ 82 ].…”
Section: Discussionmentioning
confidence: 99%
“…The influence of pro-inflammatory interleukins in the development of urogenital infections caused by E. coli has been studied in detail [53,54]. Yimer et al [55] emphasize the role of NSAIDs as potential sources of new antibacterial agents, with which the previous studies and randomized controlled trials have been conducted. The review also considers the possible antibacterial mechanism of action and NSAIDs' likely effectiveness in combination with traditional antibacterial drugs [55].…”
Section: Influence Of Nsaids On Biofilm Formation Processesmentioning
confidence: 99%
“…Yimer et al [55] emphasize the role of NSAIDs as potential sources of new antibacterial agents, with which the previous studies and randomized controlled trials have been conducted. The review also considers the possible antibacterial mechanism of action and NSAIDs' likely effectiveness in combination with traditional antibacterial drugs [55]. In studying the mechanism of action of NSAIDs on bacteria, it was found that some NSAIDs are the substrates, to which the pumping mechanisms at efflux effects among gram-negative bacteria are directed.…”
Section: Influence Of Nsaids On Biofilm Formation Processesmentioning
confidence: 99%
“…Thus, 2-((3-(3,6-dichloro- 9H -carbazol-9-yl)-2-hydroxypropyl)amino)-2-(hydroxymethyl)propane-1,3-diol ( Figure 1 - compound 10) that reduces the transmembrane potential of Gram-positive and Gram-negative bacteria and causes mislocalization of essential membrane-associated proteins, provides new opportunities for the development of potent broad-spectrum antimicrobial agents ( Eun et al., 2012 ). Another mechanism supports the idea that carbazole derivatives can interact with bacterial DNA replication and repair ( Zhang et al., 2018 ), by inhibiting the DNA polymerase ( Foxman, 2010 ), being reported to inhibit the growth of different Gram-positive and Gram-negative bacteria, such as B. cereus , Staphylococcus aureus, Listeria monocytogenes, Mycobacterium tuberculosis, M. bovis, M. neoaurum, M. smegmatis, Salmonella choleraesuis, Enterobacter aerogenes, Pseudomonas aeruginosa, Klebsiella pneumoniae, E. coli, Helicobacter pylori ) ( Lee et al., 2014 ; Addla et al., 2016 ; Yimer et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%